SIRT1 suppresses colorectal cancer metastasis by transcriptional repression of miR-15b-5p - Sun, Li-Na; Zhi, Zheng; Chen, Liang-Yan; Zhou, Qun; Li, Xiu-Ming; Gan, Wen-Juan; Chen, Shu; Yang, Meng; Liu, Yao; Shen, Tong; Xu, Yong; Li, Jian-Ming (Cancer letters, 2017)
The class III deacetylase sirtuin 1 (SIRT1), a member of the sirtuin family proteins, plays a key role in many types of cancers including colorectal cancer (CRC). Here we report that SIRT1 suppressed CRC metastasis in vitro and in vivo as a negative regulator for miR-15b-5p transcription. Mechanistically, SIRT1 impaired regulatory effects of activator protein (AP-1) on miR-15b-5p trans-activation through deacetylation of AP-1. Importantly, acyl-CoA oxidase 1 (ACOX1), a key enzyme of the fatty acid oxidation (FAO) pathway, was found as a direct target for miR-15b-5p. SIRT1 expression was positively correlated with ACOX1 expression in CRC cells and in xenografts. Moreover, ACOX1 overexpression attenuated the augmentation of migration and invasion of CRC cells by miR-15b-5p overexpression. In conclusion, our study demonstrated a functional role of the SIRT1/miR-15b-5p/ACOX1 axis in CRC metastasis and suggested a potential target for metastatic CRC therapy. •SIRT1 is a tumor suppressor gene in colorectal cancer patients.•SIRT1 suppresses CRC metastasis by blocking miR-15b-5p transcription.•SIRT1 suppresses miR-15b-5p transcription by impairing the binding of AP-1 to its promoter.•SIRT1 inhibits CRC metastasis through SIRT1/miR-15b-5p/ACOX1 axis.